Glycosylation of random IgG distinguishes seropositive and seronegative rheumatoid arthritis. (3rd April 2018) - Magorivska, I.; Döncző, B.; Dumych, T.; Karmash, A.; Boichuk, M.; Hychka, K.; Mihalj, M.; Szabó, M.; Csánky, E.; Rech, J.; Guttman, A.; Vari, S. G.; et al.
Abstract: The N-glycosylation of human immunoglobulins, especially IgGs, plays a critical role in determining affinity of IgGs towards their effector (pro- and anti-inflammatory) receptors. However, it is still not clear whether altered glycosylation is involved in only antibody-dependent disorders like seropositive rheumatoid arthritis (RA) or also in pathologies with similar clinical manifestations, but no specific autoantibodies like seronegative RA. The clarification of that uncertainty was the aim of the current study. Another study aim was the detection of specific glycan forms responsible for altered exposure of native glycoepitopes. We studied sera from seropositive RA ( n  = 15) and seronegative RA ( n  = 12) patients for exposure of glycans in native IgG molecules, followed by determination of specific glycans by capillary electrophoresis with laser-induced fluorescent detection (CE-LIF). Aged-matched groups of normal healthy donors (NHD) and samples of intravenous immunoglobulin IgG preparations (IVIG) served as controls. There was significantly stronger binding of Lens culinaris agglutinin (LCA) and Aleuria aurantia lectin (AAL) lectins towards IgG from seropositive RA compared to seronegative RA or NHD. CE-LIF analysis revealed statistically significant increases in bisecting glycans FA2BG2 ( p  = .006) and FABG2S1 ( p  = .005) seropositive RA, accompanied by decrease of bisecting monogalactosylated glycan FA2(6)G1 ( p  = .074) and non-bisecting monosialylated glycan FA2(3)G1S1 ( p  = .055). The results suggest that seropositive RA is distinct from seronegative RA in terms of IgG glycan moieties, attributable to specific immunoglobulin molecules present in seropositive disease. These glycans were determined to be bisecting GlcNAc-bearing forms FA2BG2 and FABG2S1, and their appearance increased the availability of LCA and AAL lectin-binding sites in native IgG glycoepitopes.